IMPLEMENTASI MODEL OUTDOOR LEARNING DALAM MENINGKATKAN PERILAKU MODERAT MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH (PGMI) UIN RADEN MAS SAID SURAKARTA - SUPRAPTI, SUPRAPTI; SUHARDI, MUHAMAD (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2024)
The reasons for this research are threefold. First, mastery of pedagogy for MI Teacher Education students is absolutely essential to be mastered correctly. Outdoor Learning is a learning model that can be used to actualize the pedagogical knowledge that has been provided in classroom lectures. Second, moderation is an important focus that needs to be reactivated considering that there are many cases of intolerance in society. Third, apart from lectures being held in the classroom, lectures are being held in the community so that a more moderate attitude can be more easily actualized. The aim of this research is to describe the implementation of the outdoor learning model in improving the moderate behavior of Madrasah Ibtidaiyah (PGMI) teacher education students at UIN Raden Mas Said Surakarta. This research uses a qualitative descriptive research type. The population of this study was 62 PGMI UIN Raden Mas Said 4th semester students. The results of this research describe that the outdoor learning model can relatively improve the moderate attitude of PGMI UIN RM Said Surakarta students. This means that students' learning activities are not limited by the lecture room so they can meet and communicate with many parties. From these learning activities, the habit of moderate rest has emerged and made students actualize a peaceful understanding of religion without significant conflict with society. Through a learning model like this, it can be developed by integration with various courses so that students are truly strengthened by a moderate attitude and use it as basic capital to build much closer socio-religious relations, both for religious purposes themselves and national goals more broadly. ABSTRAKAlasan penelitian ini ada tiga. Pertama, penguasaan terhadap pedagogik bagi siswa Pendidikan Guru MI adalah mutlak untuk dikuasai dengan benar. Outdoor Learning menjadi model pembelajaran yang dapat digunakan untuk mengaktualisasi keilmuan pedagogik yang telah diberikan dalam perkuliahan di kelas. Kedua, sikap moderat menjadi fokus penting yang perlu digiatkan kembali mengingat banyak terjadi kasus intoleransi di tengah masyarakat. Ketiga, selain perkuliahan dilakukan di dalam kelas, perkuliahan dilakukan di masyarakat sehingga sikap yang lebih moderat dapat lebih mudah diaktualisasikan. Tujuan penelitian ini adalah untuk mendeskripsikan implementasi model pembelajaran outdoor dalam meningkatkan perilaku moderat siswa pendidika guru madrasah ibtidaiyah (PGMI) UIN Raden Mas Said Surakarta. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Populasi penelitian ini adalah mahasiswa PGMI UIN Raden Mas Said semester 4 yang berjumlah 62 orang. Hasil dari penelitian ini mendeskripsikan model pembelajaran outdoor relatif dapat meningkatkan sikap moderat mahasiswa PGMI UIN RM Said Surakarta. Hal ini menyebabkan aktivitas belajar siswa tidak dibatasi oleh ruangan perkuliahan sehingga dapat bertemu dan berkomunikasi dengan banyak pihak. Dari aktivitas belajar itulah, pembiasaan beristirahat moderat telah muncul dan menjadikan siswa lebih mengaktualisasikan pemahaman beragama yang damai tanpa konflik yang berarti dengan masyarakat. Melalui model pembelajaran seperti ini dapat dikembangkan dengan integrasi dengan berbagai mata kuliah sehingga siswa benar-benar dibentengi sikap moderat dan menjadikannya sebagai modal dasar membangun hubungan sosial keagamaan yang jauh lebih erat, baik untuk tujuan keagamaan itu sendiri, maupun tujuan kebangsaan secara luas.